The role of TCI and TCCI indexes in regional tourism planning - Dobrila Lukić; Marko D. Petrović; Milan M. Radovanović; Tatiana N. Tretiakova; Julia A. Syromiatnikova (European Journal of Geography)
Podunavlje region in Serbia comprises 16.6% of the territory and 38.9% of the total population of the country. Due to its attractive natural values, cultural-historical monuments, ethnographic features, etc., Serbian Podunavlje has favorable conditions for the development of excursion, nautical, stationary, event, youth, rural, hunting, transit, and other kinds of tourism. Since the climate as a tourism resource and the factor of tourist migrations in the observed area has not been analyzed yet, the aim of this paper is the tourism valorization of the significance of climate using the two tourism climatic indexes: tourism climate index (TCI) and tourism climate comfort index (TCCI). To achieve it, the climate elements were first analyzed at five meteorological stations in Serbian Podunavlje: Sombor, Novi Sad, Belgrade, Veliko Gradište, and Negotin for the period 1990–2010. Then the periods favorable for tourism activities were determined according to the mentioned indexes at the given stations. The research results show that summer is certainly the most favorable season for tourism activities in the observed area since the maximum TCI values were recorded during summer, and the minimum ones during winter at all the stations. Regarding the TCCI, the most optimal values of this index were recorded in September and May. These results can further serve the tourism organizations in the municipalities in Serbian Podunavlje when considering the construction of the tourism infrastructure, marketing activities, and further affirmation of the resources for the purpose of sustainable development of tourism.